Evaluación del arbolado urbano con el uso de imágenes aéreas en dos parroquias de Quevedo - Arana Tovar, Leonel Fabricio (2022)
The purpose of this research was the evaluation of urban trees with the use of aerial images in two parishes of Quevedo, province of The Rivers. The general objective was to evaluate urban trees using aerial images in the parishes of October seventh and The Guayacán, in the canton of Quevedo, province of The Rivers. For the supervised classification, classes of sites of interest were established, of which 98 were training sites and 206 test sites for the parish of October seventh and 108 training sites and 197 test sites for the parish of the Guayacán. The use of a maximum likelihood classifier for obtaining the spectral separability between classes in which the goodness of fit of its classifier was 1.93 - 2.0 statistically generous.